Freud and a political role for psychology - van Zyl, Susan (PINS-Psychology in Society, 2025)
One of the most noticeable features of a social and political crisis is the way in which it produces in every discipline the desire to give its status as diagnostic a secure foundation, and the temptation to overstep the mark. The fear of irrelevance, while it concentrates the efforts of the human scientist upon what is most practical in his or her field, simultaneously presents the temptation to extend it, to apply that expertise to anything in the field of human experience which seems most dramatically threatened. The old adage that fear concentrates the mind may be true of individuals but it is certainly not true of the effect it has had on psychologists in South Africa. The range and extent of human suffering which confronts everyone and the wish to turn anything practical in psychology to good use is almost overwhelming, so that the cautious self-examination which would direct and focus this activity seems literally an instance of intellectual fiddling while the country burns. However admirable the wish to act as a committed psychologist might be there is surely reason to delimit the point at which psychological intervention is appropriate and direct energies where they are rationally justifiable and more likely to be efficacious.